Implementing Inertial Control for PMSG-WTG in Region 2 using Virtual Synchronous Generator with Multiple Virtual Rotating Masses - Yan, Weihang; Gao, Wei; Gao, Wenzhong; Gevorgian, Vahan (2019 IEEE Power & Energy Society General Meeting (PESGM), 2019)
With the increasing integration of renewable energy, the problems associated with deteriorating grid frequency profile and potential power system instability have become more significant. In this paper, the inertial control algorithm using Virtual Synchronous Generator (VSG) is implemented on type-4 Permanent Magnet Synchronous Generator (PMSG) - wind turbine generator (WTG). The overall nonlinear dynamic model and its small-signal linearization of PMSG-WTG using VSG is established and comprehensively analyzed. Inevitably, the direct application of VSG introduces large inertia which causes conflict between the fast-varying of available wind power and inverter control with slow dynamics, particularly in region 2 of wind turbine. Aiming to address such issue, VSG with multiple virtual rotating masses is proposed in order to improve the active power tracking performance as well as to boost inertial control of a VSG. The inertial responses are verified in a modified 10MVA IEEE 14 bus microgrid system. The assessment of the simulation results demonstrates the applicability of VSG on renewable energy generation units.